Envisioning Moroccan Topos in Arthur Leared’s “Morocco and the Moors” (1876), R.B. Cunninghame Graham’s “Mogreb-El-Acksa: A Journey in Morocco” (1898) and Budgett Meakin’s “Life in Morocco” (1905) - Aammari, Lahoucine (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Arthur Leared, Cunninghame Graham and Budgett Meakin are three British travel writers who journeyed into precolonial Morocco or Western Barbary in its tumultuous and lawless last years of its ruling Sultans. In their accounts, these travellers try to take hold of the Barbary space by making it void, vast, “uninhabited”, domestic and by erasing any signs of the Moorish Other’s life, alluring the colonialists that Western Barbary is a spatial nullity or terra nullius; it needs to be peopled and occupied. The Moorish spaces that the authors visit are regarded and perceived as anti-space as they kindle in the travellers a sense of disgust, monotony and melancholy on the one hand, and as purveyors of both erotica and exotica on the other. “Morocco and the Moors” (1876), “Mogreb-el-Aksa: A Journey in Morocco” (1898) and “Life in Morocco” (1905) share virtually the same vision towards the other’s space, a space that is unexplored, uncharted and blank. The job of these travellers is to journey into these spaces and to portray them in a vein that would contribute one way or another to the spread of discursive and rhetorical strategies that are common among their contemporaries. Therefore, there is an intertextual relation between different texts. These three travel writers try to map out Moroccan topos from their Eurocentric standpoints, but they also have recourse to different testimonies and canonical works on this space, drawing largely and exclusively on other British scholars. The voices and travellers change but space remains the same; it is fixed and frozen in an epistemological canonicity. The Moorish space is enfolded in the gaze of the traveller/seer, which is not purely innocent.
Keywords: Leared; Graham; Meakin; space; representation